Noción de aproximación del área bajo la curva utilizando la aplicación Calculadora Gráfica de GeoGebra - Ballesteros, Vladimir Alfonso; Lozano, Sébastien; Rodríguez, Óscar Iván (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This article presents the results of research project developed at the Faculty of Engineering and Basic Sciences of the Fundación Universitaria los Libertadores (Bogotá, D.C.) whose main goal was to describe and to analyze the effects of implementing a didactic strategy for teaching the concept of area under the curve, in the context of an Integral Calculus course. Cell phones devices were used as a tool intended to support the learning process considering that these devices might not be as harmful or distracting as others and, as well, that respond to the new ways of recognizing and integrating into alternative Learning communities. An experimental design of four Solomon groups was carried out with the purpose of determining the influence of an intervention mediated by the GeoGebra “Graphing Calculator” mobile application, also considering the effect of an entrance test. The results found indicate that the two groups that had the intervention based on the mobile application obtained better performance in the exit test than those groups that had an intervention with a traditional scientific calculator.